THE SPECIFIC FEATURES OF TRANSLATING FIGURATIVE EXPRESSIONS IN AMERICAN SHORT STORIES - Babajanova Yakitjan Masharipovna (Sciental Journals Publishing, 2025)
This article explores the specific features and challenges of translating figurative expressions—such as metaphors, idioms, and other stylistic devices—found in American short stories into the Uzbek language. The research emphasizes the importance of cultural and linguistic nuances in the accurate and meaningful translation of these expressions. It analyzes the contextual roles of figurative language in the original texts, offers Uzbek equivalents, and discusses various translation strategies including literal translation, adaptation, and commentary. Special attention is given to issues of semantic ambiguity, connotative meaning, and stylistic consistency. The article highlights the necessity of preserving national and cultural color in translation while ensuring clarity and coherence for the target audience.
Keywords: Figurative expressions, literary translation, metaphor, idiom, American short stories, cultural differences, translation strategies, semantic equivalence, stylistic adaptation, intercultural communication.